First report and genotyping of Dientamoeba fragilis in pet budgerigars (Melopsittacus undulatus), with zoonotic importance. (25th April 2022) - Yetismis, Gamze; Yildirim, Alparslan; Pekmezci, Didem; Duzlu, Onder; Ciloglu, Arif; Onder, Zuhal; Simsek, Emrah; Ercan, Nuri; Pekmezci, Gokmen Zafer; Inci, Abdullah
Abstract: The protozoan Dientamoeba fragilis is one of the most common parasites in the digestive system of humans worldwide. The host range and transmission routes of D. fragilis, including the role of animals, are still ambiguous with few reports from non‐human primates, sheep, rodents, pigs, a cat and a dog. In this study, we used microscopic and TaqMan qPCR analyses to investigate D. fragilis in 150 faecal samples from pet budgerigars ( Melopsittacus undulatus ) in the Central Anatolia Region of Turkey. Dientamoeba fragilis DNA was detected in 32 samples, resulting in a mean prevalence of 21.3%. In microscopic examination, trophozoites/cysts of D. fragilis were detected in 13 of 32 qPCR‐positive samples. SSU rRNA sequence analyses of the qPCR‐positive isolates identified genotype 1 of D. fragilis as predominant in budgerigars. Phylogenetic analyses of the SSU rRNA gene region clustered D. fragilis genotypes, as well as other trichomonads, in separate monophyletic clusters with bootstrap values ≥79.0. Our study provides the first evidence for the natural host status of pet budgerigars for D. fragilis and contributes to the knowledge of the epidemiology of this parasite. The high prevalence of genotype 1 of D. fragilis suggests that pet budgerigars are suitable reservoirs for zoonotic transmission. Our findings contribute to an increased awareness and knowledge of D. fragilis infections in the context of a one‐health approach. Abstract : Pet budgerigars were recorded as a new host for Dientamoeba fragilis . Phylogenetic analyses revealed the same or close genetic structure of D. fragilis in pet budgerigars as the common genotype 1 in humans, suggesting the potential for zoonotic transmission. This study contributes to increased awareness and knowledge of D. fragilis in the context of one‐health approach.